Karakteristik dan keragaman input produksi usahatani lada putih (Muntok White Pepper) di provinsi Kepulauan Bangka Belitung - Yulia Yulia; Novyandra Ilham Bahtera; Herry Marta Saputra (Fakultas Pertanian Universitas Yudharta Pasuruan, 2019)
White pepper is an annual plant which has a good prospect to be developed now and future. Kepulauan Bangka Belitung Province becomes the top white pepper producing province as well as the main exporter in Indonesia. The study aims to describe the demography of respondents that plant the white pepper and the various input production of white pepper in Kepulauan Banga Belitung Province. Descriptive qualitative analysis was employed to interpret the data. The revealed that the whiter pepper farmers had various input production. The majority of farmers was above 40 year-old, male, graduated from elementary school, farmers as main job, having above nine family members, having five non-worker family members, and married. The various input production of white pepper is land size, seeds, source of fund, fertilizer, pesticide and labor.